Experienced guilt, but not pride, mediates the effect of feedback on pro-environmental behavior. (October 2020) - Adams, Ian; Hurst, Kristin; Sintov, Nicole D.
Abstract: Feedback on one's consumption, for instance, via a carbon footprint calculator, is a common strategy used in attempts to promote pro-environmental action. Although feedback can be effective in reducing consumption, little research examines the psychological processes that may be involved. In other contexts, negative feedback can evoke guilt, whereas positive feedback can evoke pride. Pride is often associated with pro-environmental behavior, but findings are more mixed for guilt. These mixed findings may stem from heterogeneity in the measurement and operationalization of guilt across prior studies, which have measured experienced and anticipated, personal and collective guilt. The objective of the present research is to examine the roles of experienced, personal pride and guilt in an environmental feedback context, which explicitly encourages reflection on one's own past behavior. In two studies, participants from online panels completed a carbon footprint quiz and were assigned to receive bogus feedback that was framed negatively or positively, or to a control condition involving neutral feedback (Study 1, N = 397), or no feedback (Study 2, N = 544). Participants completed a measure of pro-environmental behavior one week later. In both studies, negative feedback resulted in stronger feelings of guilt, whereas positive feedback resulted in stronger feelings of pride. Both studies found that guilt, but not pride, mediated the association between feedback and subsequent pro-environmental behavior. Findings shed light on the psychological processes that occur following provision of feedback, and suggest that feedback that evokes experienced personal guilt, but not pride, may be more effective in encouraging pro-environmental behavior. Highlights: Negative or positive (or control) carbon footprint feedback was administered. Negative, not positive, feedback resulted in more pro-environmental behavior. Negative (positive) feedback resulted in stronger feelings of guilt (pride). Guilt mediated the link between feedback and pro-environmental behavior. Pride did not mediate the link between feedback and pro-environmental behavior.